2016
DOI: 10.1039/c5nr08529b
|View full text |Cite
|
Sign up to set email alerts
|

Steering microtubule shuttle transport with dynamically controlled magnetic fields

Abstract: Nanoscale control of matter is critical to the design of integrated nanosystems. Here, we describe a method to dynamically control directionality of microtubule (MT) motion using programmable magnetic fields. MTs are combined with magnetic quantum dots (i.e., MagDots) that are manipulated by external magnetic fields provided by magnetic nanowires. MT shuttles thus undergo both ATP-driven and externally-directed motion with a fluorescence component that permits simultaneous visualization of shuttle motion. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…For example, magnetic fields can be used to align or direct the movement of MTs labeled with CoFe 2 O 4 NPs. Building upon this work, we have shown that magnetic quantum dots (i.e., MagDots) in combination with patterned nanowires and microdisks can be used to control the trajectory of MTs in motion …”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…For example, magnetic fields can be used to align or direct the movement of MTs labeled with CoFe 2 O 4 NPs. Building upon this work, we have shown that magnetic quantum dots (i.e., MagDots) in combination with patterned nanowires and microdisks can be used to control the trajectory of MTs in motion …”
Section: Introductionmentioning
confidence: 89%
“…MagDots were synthesized and conjugated to biotin as described previously . Briefly, MagDots were synthesized using carboxyl‐terminated poly(styrene)‐b‐poly(ethylene oxide) (PS‐PEO) amphiphiles (Cat No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is an extension of our previous work using poly(styrene-b-ethylene oxide) (PS-b-PEO) BCPs (molecular weight 9500-b-18000 Da) to encapsulate hydrophobic NPs. [26][27][28][29] PS has been previously used for hydrophobic drug delivery 30 and may promote cellular uptake compared to hydroxyacid-based systems (ie, PLGA, poly(caprolactone)), 31 whereas the PEO block (a long chain form of PEG) creates a corona with the potential to repel opsonin proteins, reducing immunogenicity and increasing circulation times. 32 This approach is distinct from methods that encapsulate chemically similar polymers in micelles, such as those incorporating homopolymers or BCPs with common block(s), 33,34 as PLGA is chemically distinct from both PS and PEO blocks.…”
Section: Introductionmentioning
confidence: 99%